Generation de maillage et adaptation de maillage par optimisation locale - Coupez, Thierry (European Journal of Computational Mechanics, 2000)
The need of meshing in forming processes motivated the development of the meshing method which is described in this paper. A new definition for a mesh is introduced using minimal volume principle which is proven. It is shown that non conform meshes can be improved to recover a conform mesh. The generic form of the global optimization algorithm is given, based on the combination of local improvement of the neighborhood of the nodes and the edges. A layer of virtual boundary elements is introduced in order to couple the surface and the volume remeshing. A mesh size map can be introduced directly in the shape factor of elements. The mesh optimization of the modified shape factor provides implicitly the adapted mesh. Finally the adaptation cycle is presented, which consists in computing a mesh size map on the current mesh, to adapt the mesh, to compute again the mesh sie map and to adapt again until a convergence state is reached. Examples in static and dynamic adaptation are given.